Politik Hukum Sistem Upah Kerja Menurut Undang-Undang Nomor 6 Tahun 2023 Tentang Cipta Kerja - Taufiq Alamsyah; Beni Ahmad Saebani (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Labor problems both nationally and internationally in various countries are a common problem that has never been resolved properly, this happens both in developing and developed countries. Employment problems that occur in various developed and developing countries have different characteristics, this can be influenced by various fields of life in the association of human life in society and influenced by ideology, politics, law, social economy, and culture as well as the influence of the development of globalization which is very increasing and fast. The development of globalization in the field of technology and information as one that contributes to the field of employment. One of them is seen in the rapid development of globalization today in the life of society nationally and internationally, which has a major influence on the continuous association of human life and has an impact in all fields of activity in the fields of religion, economy, politics, law, social culture, and other activities nationally and internationally. The relationship between employer and employee in Islamic law is based on equal humanity. Although the structure of the company shows a hierarchy between capital owners, shareholders, and workers, Islam emphasizes that both parties are on the same level of humanity. The relationship between employer and employee is seen as a family relationship, partnership, and symbiotic mutualism. However, at present, the implementation of Law No. 6 of 2023 concerning Job Creation, especially in the field of employment, has not been able to fully answer complex problems related to wages. Therefore, alternative solutions are needed that are in accordance with the principles of wages and consider the conditions and needs of workers/laborers in Indonesia. This research aims to apply policy politics, especially related to the concept of implementing Law Number 6 of 2023 concerning Manpower from the perspective of Social Justice and Humanitarian Ethics. The implementation of the labor wage system must pay attention to the principles of justice and balance. The wages provided must be adequate to meet the needs of workers and their families, as well as provide security and protection for labor. The results show that the implementation of the Job Creation Law requires policy adjustments at the regional level through Regional Regulations that consider the economic capabilities of local companies. In the context of policy politics, the imbalance between the number of workers received and the ability of companies to fulfill wage obligations has the potential to trigger structural conflicts between companies and workers. In the perspective of Islamic politics, the relationship between employers and workers is built on the principles of social justice and human equality. Islam asserts that although there is a structural hierarchy within the company - such as capital owners, shareholders and workers - all parties are morally equal as human beings. This relationship is ideally based on the values of partnership, solidarity and symbiotic mutualism, which are in line with the principles of social justice. Therefore, wage system policies must ensure that no party is disadvantaged or feels disadvantaged, but rather create harmony and balance of interests between stakeholders. Society is politically viewed as an interconnected entity, where the common welfare becomes a collective responsibility to realize social stability and justice.